PENGGUNAAN AI TOOLS UNTUK MENINGKATKAN KUALITAS SOSIAL MEDIA UMKM ARTREE - Gunadi, Alvin Nicolas; Haikal M, Andrew; Mawardi, Viny Christanti (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
In this era of digital reform, there are approximately 97 million MSME businesses in Indonesia that often take advantage of Instagram's social media features. Artree is an MSME in the Bali region where this UMKM is engaged in healthy food in the form of protein bars. The problem faced by UMKM Artree is the lack of ability to make designs and product posting descriptions, using Instagram features. The results of the analysis at the previous PkM with the analysis tools.io, Artree's social media is still very minimal in terms of the number of posts, the number of likes, and the use of hashtags. Currently, the use of AI tools such as canva, copy.ai is increasingly being used to make it easier for beginners to get ideas for creating social media content. However, AI tools that feel easy still need to be learned so that they can be used by users who are unfamiliar with technology. For IT people, they feel that using these tools will be very easy but in fact the AI ​​tools used must be understood in terms of the concept. Different texts that will be used for promos, for advertisements or for product descriptions have different rules and different ways of using the tools. AI does not mean eliminating human involvement but is used to help improve the quality of social media content. The limited funds owned by MSMEs make them unable to hire a team of content creators or their own IT team to strengthen the content of social media material. One solution that can be done is to create content that is assisted by AI applications that make their work easier. This PkM was carried out using the AI ​​Tools training and mentoring method to produce quality Artree MSME product materials. Partner problems can be overcome if partners understand and can use AI tools to create higher quality content.